Strong Shaking From Past Cascadia Subduction Zone Earthquakes Encoded in Coastal Landforms - Sean R. LaHusen; Alex R. Grant; Jonathan P. Perkins; Devin McPhillips (Geophysical Research Letters, 2025)
Abstract Strong earthquakes along subduction zones are often devastating events, but sparse records along some tectonic margins limit our understanding of seismic hazards. Constraining shaking intensities is critical, especially in subduction zones with infrequent but large‐magnitude earthquakes like the Cascadia Subduction Zone (CSZ), where the lack of recorded ground motions has led to uncertainty in the severity and potential impacts of future earthquakes. Here we fill this observational gap with a novel inventory of quantitative estimates of past shaking intensities from geotechnical modeling of coastal landforms. One hundred fifty‐four deep‐seated landslides and 65 fragile geologic features constrain minimum and maximum peak ground accelerations, respectively. These estimates are broadly consistent with model predictions of M9 ruptures, suggesting strong shaking of 0.4–0.8 g during past CSZ earthquakes. Local discrepancies between our geologic shaking constraints and earthquake simulations may inform past rupture behavior, leading to better predictions of shaking intensity for future earthquakes.